Constraints over Greenhouse Detection using Wireless Sensor Networks (International Journal of Innovative Research in Computer Science & Technology, 2017)
Due to uneven natural distribution of rain water  it is very crucial for farmers to monitor and control the equal  distribution of water to all crops in the whole farm or as per  the requirement of the crop. There is no ideal irrigation  method available which may be suitable for all weather  conditions, soil structure and variety of crops cultures. Green  house technology may be the best solution for this solution. All  the parameters of greenhouse require a detailed analysis in  order to choose the correct method. It is observed that farmers  have to bear huge financial loss because of wrong prediction of  weather and incorrect irrigation method to crops. In this  contest with the evolution in wireless sensor technologies and  miniaturized sensor devices, it is possible to uses them for  automatic environment monitoring and controlling the  parameters of greenhouse, for Precision Agriculture (PA)  application. Now a days WSN is mainly focused on civilian  applications such as environment monitoring, object tracking  and bio-medical applications. They carry out collaborative  activities due to limited resources, such as battery, processor  and scarce memory. Nowadays, the applications of WSNs are  several and diverse, and the applications in agriculture are  still budding. One appealing WSN application is in  environmental monitoring and greenhouses, where the plant  conditions such as climate and soil does not depend on natural  agents. To manage and monitor the environmental factors,  sensors and actuators are critical. Under these circumstances,  WSN should be used to make a distributed assessment,  spreading sensors all over the greenhouse by means of  distributed clustering. This paper reveals some grave issues  when a wireless sensor network is exposed to real world  environment to monitor and manage parameters like  temperature, humidity, smoke, CO2, light and greenhouse  gases and how distributed clustering mechanisms can be  integrated within this monitoring process.
Keywords: Wireless sensor network (WSN); greenhouse; environment control; CO2 monitoring; distributed clustering